Influence of body mass index on the reliability and validity of ultrasound assessments in adolescent idiopathic scoliosis: An original research - JoJo Yiying Zou; Shirley Lok Yi Ho; Babak Hassan Beygi; Changliang Luo; Man Sang Wong (PLoS ONE, 2025)
Objectives Clinical ultrasound provides a non-invasive method to assess spinal curvature in adolescent idiopathic scoliosis (AIS). However, the reliability and validity of ultrasound assessment may be affected by body mass index (BMI). This study investigated the impact of BMI on the reliability and validity of ultrasound assessments in AIS. Design 165 participants with suspected AIS were recruited for both ultrasound and radiographic assessments. Lateral spinal curvature was measured on ultrasound imaging using the spinous process method and on X-ray using the Cobb method. The same operator performed two ultrasound scans for each participant, and two independent raters measured the images (Rater 1: 1 st and 2 nd scans; Rater 2: 1 st scan only). Intra-operator and inter-rater reliabilities were assessed using intraclass correlation coefficients (ICCs), and validity was assessed by correlating ultrasound angles with Cobb angles using Pearson’s r. Participants were categorized by BMI tertiles and BMI-for-age percentiles for subgroup analyses. Results The second BMI tertile (16.2–18.5 kg/m 2 ) exhibited the highest reliability: ICC (2,1)=0.83 (95% CI: 0.73–0.90) intra-operator and 0.88 (95% CI: 0.76–0.94) inter-rater. By BMI-for-age classification, the normal-weight group demonstrated the highest reliability (ICC = 0.78 and 0.84) and the lowest standard error of measurement (2.6° and 2.3°). Validity was strongest in the 18.1–24.4 kg/m 2 BMI group (r = 0.85), compared with 12.3–15.8 kg/m 2 (r = 0.58) and 16.0–17.7 kg/m 2 (r = 0.61). Conclusions The reliability of ultrasound assessments of spinal curvature was highest in adolescents in the second BMI tertile and in the normal-weight group, while underweight and overweight groups showed lower reliability. Correlation with Cobb angles was strongest in the 18.1–24.4 kg/m² BMI group (r = 0.85), suggesting ultrasound performs best when soft-tissue conditions are neither minimal nor excessive. These findings suggest that BMI should be considered when interpreting ultrasound measurements and when designing screening protocols for AIS.